2008
DOI: 10.1152/ajpgi.00286.2007
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of NKG2D signaling prevents the development of murine CD4+T cell-mediated colitis

Abstract: It has been recently demonstrated that NKG2D is an activating costimulatory receptor on natural killer (NK) cells, natural killer T (NKT) cells, activated CD8(+) T cells, and gammadelta T cells, which respond to cellular stress, such as inflammation, transformation, and infection. Here we show that intestinal inflammation in colitic SCID mice induced by adoptive transfer of CD4(+)CD45RB(high) T cells is characterized by significant increase of CD4(+)NKG2D(+) T cells and constitutive expression of NKG2D ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…46 Previous results had demonstrated that targeting the NKG2D-NKG2DL interaction might help prevent these pathologies. Blocking NKG2D with neutralizing anti-NKG2D monoclonal antibodies prevents the development of autoimmune diseases [47][48][49] and increases the survival of skin, bone marrow and cardiac allograft in animal models. 43,50,51 Therefore, modulation or downregulation of NKG2D by epigenetic mechanisms could be an additional therapeutic strategy for NKG2D blockage in these pathologies.…”
Section: Cells Jurkat Hut78 (Both Derived From Cd4mentioning
confidence: 99%
“…46 Previous results had demonstrated that targeting the NKG2D-NKG2DL interaction might help prevent these pathologies. Blocking NKG2D with neutralizing anti-NKG2D monoclonal antibodies prevents the development of autoimmune diseases [47][48][49] and increases the survival of skin, bone marrow and cardiac allograft in animal models. 43,50,51 Therefore, modulation or downregulation of NKG2D by epigenetic mechanisms could be an additional therapeutic strategy for NKG2D blockage in these pathologies.…”
Section: Cells Jurkat Hut78 (Both Derived From Cd4mentioning
confidence: 99%
“…Peroxidase-conjugated goat anti-rat IgG (H+L) (14-16-12) for Western blotting and Alexa Fluor 488 goat anti-rat IgG (H+L) (A11006) for immunostaining were from KPL (Gaithersburg, MD) and Invitrogen, respectively. A blocking anti-NKG2D mAb, HMG2D, was described previously (21).…”
Section: Cell Lines Abs and Reagentsmentioning
confidence: 99%
“…4) that triggers through the associated YxxM motif-containing DAP10, has been proven to be of key importance in successful treatment of UC and CD. 143 Uncovering the molecular mechanisms of NKG2D signaling, the SCHOOL model suggests the cell is translated across the membrane into protein oligomerization in CYTO milieu, thus providing a general platform for receptor-mediated signaling (Fig. 5).…”
Section: Multichainmentioning
confidence: 99%